2017
DOI: 10.3102/0162373717698221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Teachers in the Big Easy: How Organizational Context Shapes Policy Responses in New Orleans

Abstract: Although multiple-measure teacher evaluation systems have gained popularity in the United States, few studies have examined their implementation or how they are shaped by organizational context. New Orleans provides a strategic case to examine the enactment of a state teacher evaluation policy in a highly decentralized setting with variation in organizational context. Utilizing a multiple case study approach, we analyzed documents and interviews in eight case study schools. We found that schools varied in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 88 publications
4
66
1
Order By: Relevance
“…In addition, some principals reduce the pressure new evaluation systems place on teachers. Marsh et al (2017) found that some principals provided extensive coaching to teachers as they developed their lesson plan for their formal observation, thus reducing its authenticity or validity as a performance measure.…”
Section: Exercising Discretion To Modify the Evaluation Processmentioning
confidence: 99%
“…In addition, some principals reduce the pressure new evaluation systems place on teachers. Marsh et al (2017) found that some principals provided extensive coaching to teachers as they developed their lesson plan for their formal observation, thus reducing its authenticity or validity as a performance measure.…”
Section: Exercising Discretion To Modify the Evaluation Processmentioning
confidence: 99%
“…The type of data provided (Horn et al, 2015), leadership styles and the framing of conversations about the purpose of incorporating data into every-day practices (Hallett, 2010;Marsh, Bush-Mecenas, Strunk, Lincove, & Huguet, 2017;Spillane, Parise, & Sherer, 2011) and the quality of social interactions during data use matter greatly, especially when issues of trust, power, and professional identity come into play (Datnow & Castellano, 2000;Marsh & Farrell, 2015). The quandary posed by Goren (2012), "data, data, and more data-what's an educator to do?"…”
Section: The Use Of Data In Organizational Change Efforts To Achieve mentioning
confidence: 99%
“…A rich literature on policy implementation provide evidence that well-designed policies, successful in smaller pilots, often disappoint when implemented at scale (Fixsen et al, 2005). Numerous studies have found that principals do not implement teacher evaluation systems in the ways consistent with the policy’s design (Donaldson & Mavrogordato, 2018; Donaldson & Woulfin, 2018; Marsh et al, 2017; Stecher et al, 2018; Youngs, 2007; Youngs & King, 2002). The reasons underlying failed implementation are varied.…”
mentioning
confidence: 99%
“…Policies intended to improve teaching effectiveness are usually designed by states or districts but implemented by school leaders. However, these school leaders have been insufficiently featured in the teaching effectiveness literature, though this has shifted somewhat in the last decade (Donaldson & Woulfin, 2018; Grissom, 2011; Harris et al, 2010; Marsh et al, 2017). The studies that do foreground the role of principals suggest they are critical actors in policies targeting teacher evaluation and development (Burch & Spillane, 2005; Donaldson, 2013; Kardos et al, 2001; Smylie & Hart, 1999; Youngs, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation